2017
DOI: 10.1177/0021998317713832
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of polypropylene/octadecylamine lamellar-zirconium phosphate: Influence of nanofiller and screw speed

Abstract: Nanocomposite based on polypropylene and octadecylamine-modified lamellar-zirconium phosphate (PP/nano-ZrPOct) was prepared by melt processing. The action of the nanofiller and screw speed on the properties were evaluated. SEM images revealed that at highest screw speed, the higher nano-ZrPOct dispersion was achieved. In WAXD diffractrograms, some nanofiller diffraction peaks disappeared and a new peak was observed at low angle. There was evidence of increase of thermal stability although only discrete increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…To support the influence of phosphates and screw speed, the phosphate crystallographic data (single and modified) published elsewhere 27 were added in Table 2. For all nanocomposites, PP 2h diffraction peaks appeared around 14.2 (110), 16.98 (040), 18.62 (130) and 21.9 (111) associated with the a-monoclinic crystalline arrangement as reported by Mariano et al and Bafana et al 28,38 Independent on the screw speed, for the PP/ZrP nanocomposite, the ZrP diffraction angle [38][39] showed a slight shift to a low value and a feeble increase of d spacing , meaning much low PP intercalation inside the phosphate galleries. As showed in Table 2, crystallographic data of modified phosphates showed a slight displacement of pristine ZrP to low diffraction angle and d spacing weakly increased.…”
Section: Wide-angle X-ray Diffraction (Waxd)supporting
confidence: 70%
See 2 more Smart Citations
“…To support the influence of phosphates and screw speed, the phosphate crystallographic data (single and modified) published elsewhere 27 were added in Table 2. For all nanocomposites, PP 2h diffraction peaks appeared around 14.2 (110), 16.98 (040), 18.62 (130) and 21.9 (111) associated with the a-monoclinic crystalline arrangement as reported by Mariano et al and Bafana et al 28,38 Independent on the screw speed, for the PP/ZrP nanocomposite, the ZrP diffraction angle [38][39] showed a slight shift to a low value and a feeble increase of d spacing , meaning much low PP intercalation inside the phosphate galleries. As showed in Table 2, crystallographic data of modified phosphates showed a slight displacement of pristine ZrP to low diffraction angle and d spacing weakly increased.…”
Section: Wide-angle X-ray Diffraction (Waxd)supporting
confidence: 70%
“…and Bafana et al. 28,38 Independent on the screw speed, for the PP/ZrP nanocomposite, the ZrP diffraction angle 3839 showed a slight shift to a low value and a feeble increase of d spacing , meaning much low PP intercalation inside the phosphate galleries. As showed in Table 2, crystallographic data of modified phosphates showed a slight displacement of pristine ZrP to low diffraction angle and d spacing weakly increased.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…PET-OETiP displayed a shoulder at 394 C and a main peak at 416 C while in PET-JETiP appeared at 305 C and 419 C. Branda ˜o et al reported the reduction of PET thermal stability in nanocomposites with ZrP and ZrPP attributed to the aminolysis of ester bonds by amines. 17 Mariano et al 16 and Freitas et al 34 pointed out the decrease of thermal stability in nanocomposites-based PP and PA-6, respectively, owing to the presence of ZrP modified with octadecylamine. By using filler with different crystalline arrangement of those studied herein, Chowreddy and coauthors revealed the increase of PET thermal stability in recycled PET/carbon nanotube composites.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Thermal stability increased while crystallinity degree was influenced by screw speed. 16 PET composites containing 2–5 wt% of ZrP and organic–inorganic hybrid layered zirconium phenylphosphonate (ZrPP) were studied. In both cases, the addition of the fillers increased PET crystallization rate and the modulus.…”
Section: Introductionmentioning
confidence: 99%